Sexual dysfnction in Iranian pregnant women - Safieh Jamali; Leili Mosalanejad (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Sexuality is an important part of women's health, quality of life, and general well-being. There are many factors influencing the female sexual function, including psychological, physiological, couple relationship, and socio-cultural factors. Pregnancy plays an important role in the sexual function and behavior of women. Objective: This study aims to evaluate the sexual function and determine the prevalence of sexual dysfunction among women during pregnancy. Materials and Methods: The present cross-sectional study was conducted on 257 healthy pregnant women aging between18-40 years who had attended the antenatal clinic, Paymaneh Hospital, Jahrom, Iran between April and October 2011 Female Sexual Function Index (FSFI) questionnaire was used for assessing the sexual function Results: The mean age of the participants was reported as 26.45±4.49 years. In addition, 143, 69, and 45 subjects were in their 1st, 2nd, and 3rd trimesters, respectively. Comparison of the second and the third trimesters revealed a significant difference in the scores of all FSFI domains and the mean total FSFI score was reported as 19.9±22.45. Among the study subjects, 197 ones (79.1%) had sexual dysfunction (FSFI score <26.5), while only 52 (20.9%) had normal sexual function (FSFI score ≥26.5). The sexual dysfunction among pregnant women was rated as 23.4%, 30.5%, and 46.2% in the 1st, 2nd, and 3rd trimesters, respectively. Conclusion: The prevalence of sexual dysfunction is high during pregnancy and reaches higher levels in the third trimester. Therefore, pregnant women and their partners need counseling about physical and psychological changes in pregnancy